Green Economy Development through Urban Farming: A Maqāṣid Sharī'ah Review - Muhammad Syahrul Hidayat; Ahmad Munir Hamid (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2024)
This study aims to review the concept of Maqāṣid Sharī'ah in the context of green economy development through urban farming practices. Maqāṣid Sharī'ah, as a framework of Islamic ethics, provides a basis for understanding how Islamic principles can be implemented in an effort to improve economic sustainability through urban agriculture. This research uses literature analysis methods and case studies to explore Maqāṣid Sharī'ah concepts relevant to the development of a green economy. Special focus is given on how urban farming can be an effective instrument to achieve the goals of Maqāṣid Sharī'ah, such as the maintenance of religion, the maintenance of the soul, the maintenance of offspring, the maintenance of reason, and the maintenance of property. The results showed that urban farming practices can contribute positively to the fulfillment of Maqāṣid Sharī'ah's goals. In reality, urban farming not only creates new economic opportunities, but also maintains environmental sustainability, public health, and the distribution of economic justice. The implications of this research provide a foundation for the development of green economy policies and practices that are more in line with Islamic ethical values in the context of urban agriculture.